Systemic microvascular endothelial dysfunction is associated with left ventricular ejection fraction reduction in chronic Chagas disease patients. (31st October 2020) - Barata Kasal, Daniel Arthur; Britto, Ademar; Verri, Valéria; De Lorenzo, Andrea; Tibirica, Eduardo
Abstract: Objective: This study compares microvascular reactivity (MR) in chronic Chagas disease (CD) patients with healthy individuals, matched for sex and age. In addition, we evaluated the association between MR and left ventricular ejection fraction (LVEF) in patients. Methods: Acetylcholine iontophoresis was performed on the forearm skin, using laser speckle contrast imaging, to evaluate endothelium‐dependent vasodilation. Clinical data were obtained from medical records. Results: Thirty‐six patients were compared to 25 healthy individuals (controls). Vasodilation was higher in controls, when compared to patients ( p < .0001). There was a significant association between LVEF, stratified into quartiles, and MR ( p ‐value for linear trend = .002). In addition, there was no difference in MR between patients with normal LVEF and the control group. In patients, MR was independent of the presence of arterial hypertension or diabetes. Conclusions: We have shown for the first time that the reduction of MR is associated with a decrease of LVEF in a cohort of chronic CD patients. The results were not affected by comorbidities, such as hypertension or diabetes. The evaluation of systemic endothelial function may be useful to tailor therapeutic and preventive approaches, targeted at systolic left ventricular failure associated with chronic CD cardiomyopathy.